The Effect of Si/Al Ratio to Compressive Strength and Water Absorption of Ferronickel Slag-based Geopolymer - Mustofa Mustofa; Sungging Pintowantoro (IPTEK Journal of Proceedings Series, 2017)
Geopolymer material is inorganic polymers that are generally synthesized from aluminosilicate materials, such as ferronickel slag. In this study, synthesis of geopolymer material using NaOH 7 molar and Na2SiO3 solutions with different Si/Al ratio to make paste. Paste is molded in a metal mold with dimensions of 5x5x5 cm3, then released from the mold and heated in an oven at 80 °C for 24 hours. The specimens that have been heated further left at room temperature for 28 days and then tested for compressive strengthand water absorption. The results indicate a trend compressive strength increases and water absorption decreases with increasing the Si/Al ratio. The optimum condition is obtained when Si/Al ratio is 3.5.